PENGEMBANGAN KARIR, MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DI BKPP SEMARANG - Febriana, Artha (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2021)
Career development, motivation and job satisfaction are interrelated in influencing the performance of an employee. The purpose of this study was to determine the effect of career development, motivation and job satisfaction on employee performance at BKPP Semarang City. The sample in this study took the entire population of employees at BKPP Semarang City as many as 70 respondents. Data were collected using a questionnaire with a Likert scale. The results of this study indicate that career development has a significant effect on employee performance, motivation does not significantly affect employee performance and job satisfaction significantly affects employee performance. Simultaneously (together), the variables of Career Development, Motivation and Job Satisfaction have a contribution of 61.2% in influencing employee performance, while the remaining 38.8% is influenced by other variables outside of this study. Keywords: Career Development, Motivation, Job Satisfaction, Employee Performance